2019
DOI: 10.2147/ott.s191700
|View full text |Cite
|
Sign up to set email alerts
|

<p>Correlations of lncRNAs with cervical lymph node metastasis and prognosis of papillary thyroid carcinoma</p>

Abstract: Background Cervical lymph node metastasis is an important prognostic indicator for papillary thyroid carcinoma (PTC) and affects treatment strategies for PTC. lncRNAs essentially contribute to the biological functions of tumors. This study aimed to identify the lncRNAs associated with cervical lymph node metastasis and prognosis of PTC and their potential pathophysiological mechanisms. Materials and methods PTC-associated lncRNAs were selected from The Cancer Genome Atl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 38 publications
0
22
1
Order By: Relevance
“…We have shown that NEAT1 expression increases after GBM cells are exposed to radiation [ 47 ]. Although, FAM95B1 is still a poorly characterized lncRNA, one study in papillary thyroid carcinoma showed that FAM95B1 is significantly correlated with cervical lymph node metastasis, tumor staging, and prognosis [ 48 ]. FAM95B1 shows higher expression in glioblastoma (TCGA-GBM) compared with normal cortex samples from GTEx and lower-grade glioma (TCGA-LGG).…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that NEAT1 expression increases after GBM cells are exposed to radiation [ 47 ]. Although, FAM95B1 is still a poorly characterized lncRNA, one study in papillary thyroid carcinoma showed that FAM95B1 is significantly correlated with cervical lymph node metastasis, tumor staging, and prognosis [ 48 ]. FAM95B1 shows higher expression in glioblastoma (TCGA-GBM) compared with normal cortex samples from GTEx and lower-grade glioma (TCGA-LGG).…”
Section: Resultsmentioning
confidence: 99%
“…It is highly expressed in colorectal cancer tissues and is involved in the proliferation, invasion, and migration of colorectal cancer cells [ 46 ]. Additionally, FAM95B1 has been shown to be associated with thyroid cancer [ 47 ]. Limitations of our study include the lack of cell or animal experiments and its retrospective nature.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that NEAT1 expression increases after GBM cells are exposed to radiation [64]. Although, FAM95B1 is still a poorly characterized lncRNA, one study in papillary thyroid carcinoma showed that FAM95B1 is signi cantly correlated with cervical lymph node metastasis, tumor staging and prognosis [65]. FAM95B1 shows higher expression in glioblastoma (TCGA-GBM) compared with normal cortex samples from GTEx and lower-grade glioma (TCGA-LGG).…”
Section: Lncrna Expression Is Affected By Mirna Combinationmentioning
confidence: 96%